2017
DOI: 10.1111/ejn.13568
|View full text |Cite
|
Sign up to set email alerts
|

Motor deficits and beta oscillations are dissociable in an alpha‐synuclein model of Parkinson's disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterised by progressive motor symptoms resulting from chronic loss of dopaminergic neurons in the nigrostriatal pathway. The over expression of the protein alpha-synuclein in the substantia nigra has been used to induce progressive dopaminergic neuronal loss and to reproduce key histopathological and temporal features of PD in animal models. However, the neurophysiological aspects of the alpha-synuclein PD model have been poorly characterised. Hereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
3
2
0
Order By: Relevance
“…Perhaps DBS amplifies intrinsic M1 mechanisms that prevent the propagation of elevated β oscillations around the CBT loop. Indeed, HFOs also appear in M1 after severe dopamine depletion in rats, with the amount of β correlating inversely with the amount of HFOs (Brys et al ., ), consistent with the idea that the HFOs may offer some protective or homeostatic effect against exaggerated β. Further research into the mechanisms and functions of HFOs is needed to shed light on these possibilities.…”
Section: Discussionsupporting
confidence: 84%
“…Perhaps DBS amplifies intrinsic M1 mechanisms that prevent the propagation of elevated β oscillations around the CBT loop. Indeed, HFOs also appear in M1 after severe dopamine depletion in rats, with the amount of β correlating inversely with the amount of HFOs (Brys et al ., ), consistent with the idea that the HFOs may offer some protective or homeostatic effect against exaggerated β. Further research into the mechanisms and functions of HFOs is needed to shed light on these possibilities.…”
Section: Discussionsupporting
confidence: 84%
“…Perhaps DBS amplifies intrinsic M1 mechanisms that prevent the propagation of elevated β oscillations around the CBT loop. Indeed, HFOs also appear in M1 after severe dopamine depletion in rats, with the amount of β correlating inversely with the amount of HFOs [Brys et al (2017)], consistent with the idea that the HFOs may offer some protective effect against exaggerated β . Further research into the mechanisms and functions of these HFOs is needed to shed light on these possibilities.…”
Section: Discussionsupporting
confidence: 63%
“…We showed that CLDCS, altogether, had both inhibitory and excitatory effects on the spiking activity of neurons in the motor cortex and striatum (Fig 3a, 3b). A similar effect of open loop stimulation has already been established in previous research (14, 31). In addition to that, by performing dimensionality reduction on the time-series population activity of all neurons before and during bouts of locomotion, we were able to represent aggregate neural activity using principal components (PC) as locomotion unfolded over time.…”
Section: Discussionsupporting
confidence: 86%